The Interplay between Transparency, Accountability, and Corruption: A Contemporary Discourse - Muslim, Muslim; Mais, Rimi Gusliana (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
The purpose of this study is to explore the intricate interplay between transparency, accountability, and corruption within contemporary governance systems. Employing a multidisciplinary approach, the research design incorporates empirical evidence and theoretical frameworks from diverse fields to elucidate the complex dynamics of this nexus. Methodologically, the study synthesizes existing literature and conducts comparative analyses to identify key patterns and insights regarding the effectiveness of transparency-enhancing measures and accountability mechanisms in combating corruption. The findings underscore a compelling association between increased transparency and reduced levels of corruption, highlighting the pivotal role of robust accountability structures in ensuring integrity within governance systems. Implications of the study extend to both academic scholarship and practical policymaking, emphasizing the importance of adopting a holistic approach that integrates transparency and accountability measures to effectively address corruption challenges. Key implications include the need for tailored interventions that consider contextual factors, such as institutional quality and societal norms, and the imperative of leveraging technological innovations and social mobilization to empower citizens and confront corruption. This study contributes to advancing our understanding of governance dynamics and informs evidence-based strategies for promoting transparency, strengthening accountability, and combating corruption in diverse contexts.